How cancer shapes evolution, and how evolution shapes cancer - Casás-Selves, Matias (2011)
Evolutionary theories are critical for understanding cancer development at the level of species as well as at the level of cells and tissues, and for developing effective therapies. Animals have evolved potent tumor suppressive mechanisms to prevent cancer development. These mechanisms were initially necessary for the evolution of multi-cellular organisms, and became even more important as animals evolved large bodies and long lives. Indeed, the development and architecture of our tissues were evolutionarily constrained by the need to limit cancer. Cancer development within an individual is also an evolutionary process, which in many respects mirrors species evolution. Species evolve by mutation and selection acting on individuals in a population; tumors evolve by mutation and selection acting on cells in a tissue. The processes of mutation and selection are integral to the evolution of cancer at every step of multistage carcinogenesis, from tumor genesis to metastasis. Factors associated with cancer development, such as aging and carcinogens, have been shown to promote cancer evolution by impacting both mutation and selection processes. While there are therapies that can decimate a cancer cell population, unfortunately, cancers can also evolve resistance to these therapies, leading to the resurgence of treatment-refractory disease. Understanding cancer from an evolutionary perspective can allow us to appreciate better why cancers predominantly occur in the elderly, and why other conditions, from radiation exposure to smoking, are associated with increased cancers. Importantly, the application of evolutionary theory to cancer should engender new treatment strategies that could better control this dreaded disease.